Comparative Mitogenomics Provides Valuable Insights for the Phylogeny and New DNA Barcodes of Ganoderma - Ti-Qiang Chen; Chi Yang; Xiao-Lan Xu; Lin Yang; Huan-Qing He; Meng-Ting Weng; Zheng-He Ying; Xiao-Kun Shi; Meng-Guang Ding (Journal of Fungi)
Ganoderma is the most important genus in the family Ganodermataceae; many species have attracted much attention and widely cultivated because of their medicinal values, but so far, not a sequenced mitogenome derived from dikaryon strains has been explicitly recorded. Herein, four novel mitogenomes of commonly cultivated Ganoderma (G. leucocontextum H4, G. lucidum G6, G. sinense MZ96 and G. tsugae SS) were de novo assembled and given detail functional annotations. Collinearity analysis revealed that the four mitogenomes shared 82.93–92.02% similarity with their corresponding reference mitogenomes at the nucleotide level. A total of 15 core protein-coding genes (PCGs), along with rrnL and rrnS (mtLSU and mtSSU) were chosen as potential candidates for constructing their individual phylogenetic trees. These trees were compared with those derived from the concatenated sequences of 15 core PCGs. And finally, we found that the atp9 and nad4L were the most reliable markers for the phylogenetic analysis of Ganoderma and chosen as standard sequences to generate new DNA barcodes. This finding was further verified by comparing it against almost all available Ganoderma mitogenomes in the NCBI, with Trametes versicolor (Polyporaceae) and Rigidoporus microporus (Meripilaceae) as two outgroups. A total of 52 mitogenomes from three families were highly conserved, with identical gene lengths for atp9 (222 bp) and nad4L (267 bp). These genes were capable of distinguish distinctly different various species, which are grouped into separate clades within the phylogenetic trees. The closest related clades (I and II), including at least 30 samples of the three classical taxonomic species (G. lingzhi, G. sichuanense and G. lucidum), differed in only one SNP. The single base mutation rate increased with the evolutionary divergence of the phylogenetic clades, from two to three SNPs in earlier clades (e.g., clade IV containing G. leucocontextum) to five to six SNPs in later clades (e.g., clade X containing G. sinense). Despite these variations between species, the atp9 and nad4L genes of Ganoderma mitogenomes consistently encoded the same ATP synthase F0 subunit c (73 aa) and NADH dehydrogenase subunit 4L (88 aa). These two genes have been identified as reliable markers of new DNA barcodes, offering valuable insights and contributing significantly to understanding the evolutionary relationships and phylogeny of the Ganoderma genus and even the Ganodermataceae family.